The role of service learning in promoting musical creativity and educational belief transformation among Pre-service music teachers - Yuqian Du; Mohd Mahzan Awang; Khairul Azhar Jamaludin (Environment and Social Psychology, 2025)
This study employs a quasi-experimental design to explore the mechanisms by which service-learning influences the creativity and educational beliefs of preservice music teachers. Sixty-two music education major students from a normal university were selected: the experimental group (n=32) participated in a 16-week community music service project, while the control group (n=30) received regular coursework. Multidimensional data on music creativity, educational beliefs, environmental awareness, and social support were collected through pretest, midtest, and posttest measurements. Results showed: the experimental group’s total music creativity score increased from a pretest mean of 68.45 (SD=8.23) to a posttest mean of 89.72 (SD=7.56), representing a 31.08% increase, significantly higher than the control group’s increase from 67.89 to 72.34, a 6.55% increase (p<0.001, Cohen’s d=2.34); educational beliefs increased from 2.8 to 4.7 points, a 67.9% increase, with social responsibility increasing by 80.8%, while the control group increased only 14.8% (p<0.001, d=3.26). Mediation analysis revealed that environmental awareness explained 32.4% of creativity growth and 36.9% of belief transformation; moderation analysis found that social support strengthened the effect of environmental awareness (interaction term β=0.18-0.21, p=0.002); reflection depth analysis indicated that the critical reflection group’s outcomes were 75-127% higher than the descriptive reflection group (η²=0.695-0.758). The study confirms that service-learning promotes preservice teacher professional development through multiple mechanisms of "authentic context → environmental awareness → reflective processing → social support," providing empirical support for innovative teacher education models. Theoretically, this study constructs an ecological action model of "authentic context → environmental awareness → reflective processing → social support," breaking through the traditional linear training paradigm and enriching the interdisciplinary theory of service-learning and music education. Practically, the study provides an operational pathway for higher music education reform.